Implementasi Problem Based Learning Berbantuan Mathigon untuk Meningkatkan Kemampuan Bernalar Kritis Siswa Kelas 5 pada Materi Bangun Datar - Nanang Rianto (TA'DIBAN, 2025)
The study results indicate that the implementation of the Problem Based Learning (PBL) model supported by the Mathigon platform can enhance students' active participation and deepen their understanding of geometric concepts. Data were collected through observation, interviews, documentation, and students' work, which were analyzed qualitatively in accordance with the guidelines of Miles and Huberman. This analysis reveals an increase in student participation as well as the development of critical thinking skills, such as analyzing, comparing, and drawing logical conclusions during the learning process. These improvements are supported by data triangulation from classroom discussions, activity observations, and students’ works. The findings demonstrate that the integration of PBL and Mathigon is effective in creating an active and reflective learning environment and in improving elementary students' critical thinking abilities. This research recommends applying this approach as an innovative strategy for primary mathematics instruction.